A preliminary study on polysaccharide extraction, purification, and antioxidant properties of sugar-rich filamentous microalgae Tribonema minus - Huo, Shuhao; Wang, Huiying; Chen, Jing; Hu, Xinjuan; Zan, Xinyi; Zhang, Cunsheng; Qian, Jingya; Zhu, Feifei; Ma, Haile; Elshobary, Mostafa (Journal of applied phycology, 2022)
The total polysaccharide content of the sugar-rich filamentous microalga Tribonema minus (Xanthophyceae, Tribonematales) under 2% CO 2 was up to 50%. The optimal conditions for the extraction of polysaccharide by hot water extraction-ethanol deposition were as follows: A maximum polysaccharide yield of 27.25% was obtained under the optimized conditions of extraction temperature 80°C, extraction time of 2 h, pH 9, and liquid to raw material 0.5:1 mL mg −1 . The crude polysaccharides were mainly acidic polysaccharides containing sulfate groups and uronic acid, and the contents of which were 14.57% and 42.21 mg g −1 , respectively. The crude polysaccharide was mainly composed of rhamnose, arabinose, xylose, mannose, glucose, and galactose with a molar ratio of 0.31:0.26:0.40:0.42:1.00:0.47. In addition, the polysaccharide had a potential antioxidant activity in vitro. The scavenging effect and reducing power of polysaccharides increased with the increase of polysaccharide concentration. The scavenging effect was 56.11%, 75.6%, and 61.89% for 1,1-diphenyl-2-picrylhydrazyl free radical (DPPH), superoxide, and hydroxyl radicals at a concentration of 2 mg L −1 , respectively. Hence, T. minus polysaccharides could be a source of natural antioxidants that might be used in foods or pharmaceuticals.